Renal Ischemia/Reperfusion Injury in Diabetic Rats: The Role of Local Ischemic Preconditioning. (26th January 2016) - Ozbilgin, Sule; Ozkardesler, Sevda; Akan, Mert; Boztas, Nilay; Ozbilgin, Mucahit; Ergur, Bekir Ugur; Derici, Serhan; Guneli, Mehmet Ensari; Meseri, Reci
Abstract : Background . The aim of this study was to evaluate the effects of local ischemic preconditioning using biochemical markers and histopathologically in the diabetic rat renal IR injury model. Methods . DM was induced using streptozotocin. Rats were divided into four groups: Group I, nondiabetic sham group (n = 7 ), Group II, diabetic sham group (n = 6 ), Group III, diabetic IR group (diabetic IR group, n = 6 ), and Group IV, diabetic IR + local ischemic preconditioning group (diabetic IR + LIPC group, n = 6 ). Ischemic renal injury was induced by clamping the bilateral renal artery for 45 min. 4 h following ischemia, clearance protocols were applied to assess biochemical markers and histopathologically in rat kidneys. Results . The histomorphologic total cell injury scores of the nondiabetic sham group were significantly lower than diabetic sham, diabetic IR, and diabetic IR + LIPC groups. Diabetic IR group scores were not significantly different than the diabetic sham group. But diabetic IR + LIPC group scores were significantly higher than the diabetic sham and diabetic IR groups. Conclusion . Local ischemic preconditioning does not reduce the risk of renal injury induced by ischemia/reperfusion in diabetic rat model.